2022
DOI: 10.1111/jvs.13151
|View full text |Cite
|
Sign up to set email alerts
|

Late‐season drought exerts more negative effects on plant diversity and cover than early‐season drought through changing soil moisture in a semi‐arid grassland

Abstract: Questions Drought timing during the growing season can profoundly influence plant diversity and cover, with subsequent impacts on ecosystem functions and services in terrestrial environments. However, the different responses of plant communities to drought in different periods of the growing season remain uncertain. Location The research was conducted in a semi‐arid grassland at the Duolun Restoration Ecology Research and Demonstration Station, in Inner Mongolia, China. Methods The responses of plant species r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that rainfall changes can significantly affect species richness, Simpson dominance index and the Shannon-Wiener diversity index [52] but that they have no significant effect on Pielou evenness index [53]. Experiments simulating extreme drought have found that drought can reduce plant height, coverage and diversity, and ultimately reduce productivity [54]. Consistent with the results of previous studies, the CWM height and coverage of −60% and −60 d in our study were reduced, and −60% significantly reduced the Shannon-Wiener diversity index and increased Simpson dominance index.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that rainfall changes can significantly affect species richness, Simpson dominance index and the Shannon-Wiener diversity index [52] but that they have no significant effect on Pielou evenness index [53]. Experiments simulating extreme drought have found that drought can reduce plant height, coverage and diversity, and ultimately reduce productivity [54]. Consistent with the results of previous studies, the CWM height and coverage of −60% and −60 d in our study were reduced, and −60% significantly reduced the Shannon-Wiener diversity index and increased Simpson dominance index.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between abiotic conditions and phylogenetic diversity of co-flowering modules will be important to elucidate, as phylogenetic diversity promotes ecosystem stability and soil microbial diversity [81,82]. Low soil moisture may drive low phylogenetic diversity, as it causes declines in species richness and biomass production [8386]. However, soil moisture is affected by snowmelt timing and precipitation from summer thunderstorms and has significant interannual variability [8790], which would not explain our consistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there is some evidence that precipitation patterns matter most for ecosystem function during drought years (Felton et al., 2020), but other research challenges this notion (Liu, Jin, et al., 2022). Evidence is also mixed regarding the sensitivity of ecosystems to drought timing/seasonality (Denton et al., 2017; Felton & Goldsmith, 2023; Hallett et al., 2019; McAuliffe & Hamerlynck, 2010; Miao et al., 2022) as well as drought duration (Carroll et al., 2021; Estiarte et al., 2016; Evans et al., 2011; Jentsch et al., 2011; Wang et al., 2021; Xu et al., 2021). Indeed, assessments of the relative impacts of the magnitude versus the duration of drought and how effects of the duration of drought may be contingent on magnitude are critically needed (Felton et al., 2021).…”
Section: Looking Forwardmentioning
confidence: 99%